ANALISIS DUKUNGAN KELUARGA TERHADAP STRES KERJA TENAGA KESEHATAN DI RSUD WARU KAB. PAMEKASAN - Atikah Rahadiani Basar; Rifaatul Laila Mahmudah; Eka Diah Kartiningrum (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Health-care workers are confronted with condition that demand to always provide optimum health-care service. It causes health-care workers to cope with stress at work. Health-care workers may experience stress at work when the job demand are not suitable with their abilities. There are several factors that can cause work stress to health-care workers, including family's support. The purpose of this study is to know family's support analyzes for the work stress on health-care workers in RSUD Waru, Pamekasan Regency. The method of this research is a type of quantitative research using an observational analytic design through cross sectional approach with research focus is directed to know the effect of family support for the work stress of health-care workers in RSUD Waru, Pamekasan Regency. The number of population is 122 people and the number of samples are 55 respondents which are taken by Simple Random Sampling technique. The result of linear regression shows Fcount value is 45,769 with P Value (0.000) it means that there is influence of family support for work stress. The value of determinant coefficient shows 0.463 which means that 46.3% of work stress is determined by family support while the remaining amount to 53.7% is effected by other factors. In this study, the result is found that there is an influence between family support with stress work of health-care workers in RSUD Waru, Pamekasan Regency. Family's support has negative relation towards the work stress that is experienced by health-care workers. Health care workers who receive sufficient family support will experience less work stress.